2006
DOI: 10.1111/j.1474-8673.2006.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonist and antagonist sensitivity of non‐selective cation channel currents evoked by muscarinic receptor stimulation in bovine ciliary muscle cells

Abstract: 1 In the bovine ciliary muscle, stimulation of muscarinic receptors with carbachol (CCh) opens two types of non-selective cation channels (NSCCS and NSCCL) with widely different unitary conductances (100 fS and 35 pS). Here we examined the dependence of the activity of NSCCS on the agonist (CCh) concentration by whole-cell voltage clamp in freshly isolated bovine ciliary muscle cells. We also examined the sensitivity of CCh-evoked NSCCS currents to several muscarinic receptor antagonists. 2 The voltage clamp e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The NSCCS component in contrast quickly decayed and almost disappeared within 10 min in all cells (Figure 10a). In our previous whole‐cell clamp experiments, we have also repeatedly noticed that, unlike the NSCCL component, the NSCCS component of CCh‐evoked NSCC currents tends to become smaller when stimulation by CCh is repeated ( Takai et al ., 1997 , 2004 ; Sugawara et al ., 2006 ). YM (10 μ M ) had no effect on the NSCC current evoked by GTPγS (Figure 10a; examined in five cells).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NSCCS component in contrast quickly decayed and almost disappeared within 10 min in all cells (Figure 10a). In our previous whole‐cell clamp experiments, we have also repeatedly noticed that, unlike the NSCCL component, the NSCCS component of CCh‐evoked NSCC currents tends to become smaller when stimulation by CCh is repeated ( Takai et al ., 1997 , 2004 ; Sugawara et al ., 2006 ). YM (10 μ M ) had no effect on the NSCC current evoked by GTPγS (Figure 10a; examined in five cells).…”
Section: Resultsmentioning
confidence: 99%
“…However, as demonstrated in the bovine and human ( Suzuki, 1983 ) and in the canine species ( Ito and Yoshitomi, 1986 ), the ciliary muscle lacks, or is deficient in, voltage‐gated Ca 2+ entry pathways. In previous experiments on the bovine ciliary muscle, we have identified two non‐selective cation channels (NSCCs) with different unitary conductances (35 pS and 100 fS), which are opened upon stimulation of M 3 receptors, and have shown that the Ca 2+ influx through either or both of these NSCCs is responsible for the tonic phase of contraction produced by muscarinic stimulation ( Takai et al ., 2004 ; Sugawara et al ., 2006 ). However, little is known about how signals are transmitted from the receptor to the NSCCs to induce the Ca 2+ influx.…”
Section: Introductionmentioning
confidence: 99%
“…In bovine ciliary muscle, gene expression and immunolocalisation analysis revealed the presence of TRPC1, TRPC3, TRPC4 and TRPC6. These TRPs are regarded as possible molecular candidates for receptor-operated cation channels [25]. Taken together, these studies suggest that ciliary muscle function can be modulated by controlling the activation status of these different TRPC subfamily members.…”
Section: Ciliary Musclementioning
confidence: 99%
“…(c) Addition of 1 µmol/l okadaic acid did not cause any change (98.1 ± 1.2%, n = 8, P = 0.16) in pre-contracted BCM with 2 µmol/l CCh.) (1,2,3). Acetylcholine binds to G q/11 -coupled M 3 receptors (3, 4) and induces rapid Ca 2+ release from the sarcoplasmic reticulum, followed by a sustained Ca 2+ influx through non-selective cation channels (NSCC) on the plasma membrane of ciliary myocytes (5,6,7). …”
Section: Introductionmentioning
confidence: 99%